Answer:
Let R = cost per foot of redwood, and
let P = cost per foot of pine.
The 1st sentence gives us 60 ft * R + 90 ft * P = $303, and
the 2nd sentence gives us 90 ft * R + 60 ft * P = $357.
So this is two equations and two unknowns, so we should be able to solve these.
Solve the first equation for P: 60 ft * R + 90 ft * P = $303
Subtract 60 ft * R from both sides of the equation: 90 ft * P = $303 - 60 ft * R
Now divide both sides of the equation by 90 ft: P = ($303 - 60 ft * R) / 90 ft = $101 / 30 ft - 2/3 * R
Next, substitute P into the second equation: 90 ft * R + 60 ft * P = $357
so we then have 90 ft * R + 60 ft * [$101 / 30 ft - 2/3 * R] = $357.
Now solve for R (remember, parentheses, exponents, multiplication and division, addition and subtraction):
90 ft * R + [$202 - 40 ft * R] = 50 ft * R + $202 = $357, or 50 ft * R = $155; so R = $155 / 50 ft = $3.10 / ft.
Now we can substitute this value for R into the first equation and solve for P: 60 ft * R + 90 ft * P = $303
so we then have 60 ft * $3.10 / ft + 90 ft * P = $303, or $186 + 90 ft * P = $303.
Subtracting $186 from both sides of the equation, and then dividing by 90 ft, we have P = $1.30 / ft
So P = $1.30/ft, and R = $3.10/ft.
To check this answer, plug both into the second equation:
90 ft * R + 60 ft * P = $357
90 ft * $3.10/ft + 60 ft * $1.30/ft = $279 + $78 = $357